Emotional reactivity in a clinical sample of patients with eating disorders and nonsuicidal self-injury. (November 2017) - Smith, Kathryn E.; Hayes, Nicole A.; Styer, Denise M.; Washburn, Jason J.
Abstract: Emotional reactivity is theorized to contribute to both eating disorders (ED) and nonsuicidal self-injury (NSSI). Although EDs and NSSI frequently co-occur, no study has examined emotional reactivity in individuals with both conditions. This study examined the following hypotheses in a large clinical sample ( N = 648): (1) patients with co-occurring ED and NSSI would report higher emotional reactivity and more severe clinical characteristics; (2) among those with EDs, patients with bulimia nervosa (BN) would be more likely to report NSSI and evidence higher emotional reactivity compared to those with anorexia nervosa (AN); and (3) higher emotional reactivity would be associated with worse treatment outcomes. Data were collected at admission and discharge from inpatient, partial hospitalization, and intensive outpatient treatment programs for EDs or NSSI. The NSSI-only and co-occurring groups reported significantly higher emotional reactivity than the ED-only group. Among those with EDs, individuals with BN reported higher emotional reactivity and were more likely to engage in NSSI compared to those with AN. Emotional reactivity was inconsistently related to treatment outcomes among the co-occurring and ED-only groups. In sum, results highlight the importance of emotional reactivity in clinical presentations, particularly when NSSI is present. Highlights: Research suggests EDs and NSSI are associated with elevated emotional reactivity. We assessed emotional reactivity in ED-only, NSSI-only, and co-occurring groups. Emotional reactivity was highest in the co-occurring and NSSI-only groups. Those with bulimia reported higher emotional reactivity than those with anorexia. Emotional reactivity was not consistently related to treatment outcomes.